Distribución espacial del carbono orgánico del suelo en el sector Huacapamba, parroquia Jimbilla, cantón Loja. - Jimenez Peña, Estefania Carolina (2022)
The Huacapamba area belonging to the Jimbilla parish is characterized by local production based on agriculture, but much more on livestock, which has caused the loss of soil quality and natural ecosystems. This is due to the lack of information from agricultural producers about the importance of soil organic carbon (SOC). In this research, the spatial distribution and the influence of factors such as vegetation, land use, topography and the physical and chemical properties of the soil on the storage of soil organic carbon were analyzed. An area of 30 hectares within a farm in the Huacapamba neighborhood was studied, where 10 sampling points were established in each identified land use and two types of samples were taken in the first 30 cm of depth: a disturbed one to determine the organic matter, texture and C/N ratio; and an undisturbed one to determine the bulk density. To analyze their spatial distribution, the IDW interpolation method was used in the ArcGis software. The following results were obtained: 1) The total COS content was 1 595,50 t ha-1. Secondary forest contributed 41,15%, primary forest 33,15% and grassland 25,70%. Therefore, the areas covered by forests presented higher SOC storage compared to grasslands. 2) The chemical properties (organic matter and total nitrogen) and the vegetation (close matter, Shannon biodiversity index and carbon in trees) had a greater effect on the COS content. Topography (slope and elevation) and physical properties (apparent density) were the variables that presented the least correlation. Keywords: Soil; organic carbon; spatial distribution; influencing factors.